(untitled) (Journal on studies and research of academic knowledge, 2021)
The study refers to the Ava Guarani people from Paraná, who, despite all the adversities they have experienced and continue to experience due to the forced displacement from their ancestral territory, are resilient and mentally healthy. The objective was to determine the influence of psychological and sociocultural factors that support and/or enable the development of resilient traits and contribute to their mental health. We worked with seven Ava Guarani communities in Paraguay as an exploratory study, with a qualitative method and ethnographic approach, using participant observation and interview techniques. According to the results, the main key to mental health is to be in peace / py’aguapy. Factors that contribute to this state of integral wellbeing are: positive self-image, sense of humor, collective self-esteem, spirituality and identity in connection with nature, hope for a promising future, being word-soul loved by their Creator, matrilocal organization, ties with the extended family, freedom and the territory where to develop in Guarani identity, are determinants of the strength they possess as a resilient culture.